Enhancing thai fifth-year medical students’ knowledge and attitudes toward palliative care through active learning methods - Thammasin Ingviya; Orapan Fumaneeshoat; Pawita Limsomwong (BMC Medical Education)
Abstract Background Palliative care is an essential component of holistic medical education, addressing physical, psychological, social, and spiritual needs in patients with life-limiting illnesses. However, medical students often report inadequate training and low confidence in providing palliative care. Active learning methods, including team-based learning (TBL), flipped classrooms (FC), and experiential learning via home visits, have been proposed to enhance palliative care education. This study aimed to assess the effectiveness of these active learning strategies in improving the knowledge and attitudes of fifth-year medical students toward palliative care. Methods A cross-sectional study was conducted at the Faculty of Medicine of the Prince of Songkla University in Thailand. Fifth-year medical students participated in a structured palliative care curriculum integrating TBL, FC, and experiential learning via palliative home visits. Changes in their knowledge and attitudes were measured using pre- and post-course questionnaires, which were validated by experts and pilot-tested for reliability (Cronbach’s alpha = 0.71). Data analysis employed paired t-tests and Wilcoxon signed-rank tests to evaluate changes in knowledge and attitudes. Results A total of 251 students completed the pre-test, with 62 of them also completing the post-tests. Significant improvements were observed in the students’ knowledge of palliative care principles (p < 0.001), assessment techniques (p < 0.001), pain management (p < 0.001), and advance care planning (p < 0.001), while no significant changes were noted in their knowledge of physical (p = 0.726) or psychological symptom management (p = 0.594). Attitudinal changes included decreased perception of the difficulty of palliative care (p < 0.001) and increased recognition of its necessity (p < 0.001). However, students also reported significantly higher levels of emotional stress (p = 0.006) and increased feelings of hopelessness (p = 0.008). In contrast, their confidence in managing end-of-life care did not improve significantly (p = 0.238). Conclusions Integrating TBL, FC, and experiential learning significantly enhanced students’ knowledge and corrected misconceptions about palliative care. However, the emotional burden of palliative care remained a challenge, highlighting the need for coping skill training and additional support in medical curricula. Future research should explore longitudinal interventions which might better reinforce confidence in end-of-life care. Clinical trial number Not applicable.